Carpentry and construction - Miller, Mark R.; Miller, Rex (New York, N.Y. McGraw-Hill Education, 2016)
A comprehensive guide to carpentry and construction that details each step in home building with over 1,500 photographs and illustrations on foundations, framing, roofing, windows, wiring, plumbing, solar heating, skylights, fences, sewage systems, and more.
Keywords: Carpentry; House construction; Electronic books